VD_FINDINFO HC / 2020 / 299 vom 12. Juni 2020 - VD Tribunal cantonal (2020)
DROIT DE VOISINAGE, REJET DE LA DEMANDE, TRAVAUX DE CONSTRUCTION, IMMISSION, LIEN DE CAUSALITÉ | 641 al. 2 CC, 679 CC, 679a CC, 685 CC, 41 CO